Electrochemical selenium- and iodonium-initiated cyclisation of hydroxy-functionalised 1,4-dienes - Röse, Philipp; Emge, Steffen; Yoshida, Jun-ichi; Hilt, Gerhard (Beilstein Journal of Organic Chemistry, 2015)
The cobalt(I)-catalysed 1,4-hydrovinylation reaction of allyloxytrimethylsilane and allyl alcohol with substituted 1,3-dienes leads to hydroxy-functionalised 1,4-dienes in excellent regio- and diastereoselective fashion. Those 1,4-dienols can be converted into tetrahydrofuran and pyran derivatives under indirect electrochemical conditions generating selenium or iodonium cations. The reactions proceed in good yields and regioselectivities for the formation of single diastereomers.
Keywords: cyclic ethers; cyclisation; 1,4-dienes; electrochemistry; iodonium; selenium

(untitled) - Hilt, G. (Eur. J. Org. Chem., 2012)

(untitled) - Hilt, G. (Synlett, 2011)

(untitled) - RajanBabu, T. V. (Synlett, 2009)

(untitled) - RajanBabu, T. V. (Chem. Rev., 2003)

(untitled) - Arndt, M.; Dindaroğlu, M.; Schmalz, H.-G.; Hilt, G. (Org. Lett., 2011)

(untitled) - Arndt, M.; Dindaroğlu, M.; Schmalz, H.-G.; Hilt, G. (Synthesis, 2012)

(untitled) - Hilt, G.; Arndt, M.; Weske, D. F. (Synthesis, 2010)

(untitled) - Erver, F.; Kuttner, J. R.; Hilt, G. (J. Org. Chem., 2012)

(untitled) - Kersten, L.; Roesner, S.; Hilt, G. (Org. Lett., 2010)

(untitled) - Harmange, J.-C.; Figadère, B. (Tetrahedron: Asymmetry, 1993)

(untitled) - Faulkner, D. J. (Nat. Prod. Rep., 1998)

(untitled) - Faul, M. M.; Huff, B. E. (Chem. Rev., 2000)

(untitled) - Lorente, A.; Lamariano-Merketegi, J.; Albericio, F.; Álvarez, M. (Chem. Rev., 2013)

Organic Electrochemistry - Lund, H.; Hammerich, O. (Marcel Dekker, Inc., 2001)
ISBN:0-8247-0430-4.

(untitled) - Moeller, K. D. (Tetrahedron, 2000)

(untitled) - Sperry, J. B.; Wright, D. L. (Chem. Soc. Rev., 2006)

(untitled) - Yoshida, J.; Kataoka, K.; Horcajada, R.; Nagaki, A. (Chem. Rev., 2008)

(untitled) - Steckhan, E. (Angew. Chem., Int. Ed. Engl., 1986)

(untitled) - Suga, S.; Matsumoto, K.; Ueoka, K.; Yoshida, J. (J. Am. Chem. Soc., 2006)

(untitled) - Uneyama, K.; Fujibayashi, S.; Torii, S. (Tetrahedron Lett., 1985)

(untitled) - Vukićević, R.; Konstantinović, S.; Mihailović, M. L. (Tetrahedron, 1991)

(untitled) - Konstantinović, S.; Vukićević, R.; Mihailović, M. L. (Tetrahedron Lett., 1987)

(untitled) - Torii, S.; Uneyama, K.; Ono, M.; Tazana, H.; Matsunami, S. (Tetrahedron Lett., 1979)

(untitled) - Torii, S.; Uneyama, K.; Ono, M. (Tetrahedron Lett., 1980)

(untitled) - Torii, S.; Uneyama, K.; Ono, M. (Tetrahedron Lett., 1980)

(untitled) - Torii, S.; Uneyama, K.; Ono, M.; Bannou, T. (J. Am. Chem. Soc., 1981)

(untitled) - Uneyama, K.; Takano, K.; Torii, S. (Tetrahedron Lett., 1982)

(untitled) - Chamberlin, A. R.; Dezube, M.; Dussault, P.; McMills, M. C. (J. Am. Chem. Soc., 1983)

(untitled) - Labelle, M.; Guindon, Y. (J. Am. Chem. Soc., 1989)

(untitled) - Still, W. C.; Schneider, M. J. (J. Am. Chem. Soc., 1977)

(untitled) - Hajra, S.; Maji, B.; Karmakar, A. (Tetrahedron Lett., 2005)

(untitled) - Hartung, J.; Kneuer, R.; Laug, S.; Schmidt, P.; Špehar, K.; Svoboda, I.; Fuess, H. (Eur. J. Org. Chem., 2003)

(untitled) - Denmark, S. E.; Burk, M. T. (Proc. Natl. Acad. Sci. U. S. A., 2010)

(untitled) - Fujioka, H.; Maehata, R.; Wakamatsu, S.; Nakahara, K.; Hayashi, T.; Oki, T. (Org. Lett., 2012)

(untitled) - Fang, C.; Paull, D. H.; Hethcox, J. C.; Shugrue, C. R.; Martin, S. F. (Org. Lett., 2012)

(untitled) - Hennecke, U.; Müller, C. H.; Fröhlich, R. (Org. Lett., 2011)

(untitled) - Barluenga, J.; González, J. M.; Campos, P. J. (Angew. Chem., Int. Ed. Engl., 1985)

(untitled) - Takaku, K.; Shinokubo, H.; Oshima, K. (Tetrahedron Lett., 1996)

(untitled) - Zhang, H.; Mootoo, D. R. (J. Org. Chem., 1995)

(untitled) - Curini, M.; Epifano, F.; Marcotullio, M. C.; Montanari, F. (Synthesis, 2004)

(untitled) - Bailey, A. D.; Cherney, S. M.; Anzalone, P. W.; Anderson, E. D.; Ernat, J. J.; Mohan, R. S. (Synlett, 2006)

(untitled) - Miller, L. L.; Watkins, B. F. (Tetrahedron Lett., 1974)

(untitled) - Srebnik, M.; Mechoulam, R. (J. Chem. Soc., Chem. Commun., 1984)

(untitled) - Chavan, S. P.; Sharma, A. K. (Tetrahedron Lett., 2001)

(untitled) - Jones, C. C. (Application of Hydrogen Peroxide and Derivatives, 1999)
ISBN:978-0-85404-536-5.

(untitled) - Yoshida, J.; Suga, S.; Suzuki, S.; Kinomura, N.; Yamamoto, A.; Fujiwara, K. (J. Am. Chem. Soc., 1999)

(untitled) - Suga, S.; Suzuki, S.; Yamamoto, A.; Yoshida, J. (J. Am. Chem. Soc., 2000)

(untitled) - Yoshida, J.; Suga, S. (Chem. – Eur. J., 2002)

(untitled) - Nokami, T.; Ohata, K.; Inoue, M.; Tsuyama, H.; Shibuya, A.; Soga, K.; Okajima, M.; Suga, S.; Yoshida, J. (J. Am. Chem. Soc., 2008)

(untitled) - Ashikari, Y.; Shimizu, A.; Nokami, T.; Yoshida, J. (J. Am. Chem. Soc., 2013)

(untitled) - Morofuji, T.; Shimizu, A.; Yoshida, J. (Angew. Chem., Int. Ed., 2012)

(untitled) - Torii, S.; Inokuchi, T.; Akahosi, F.; Kubota, M. (Synthesis, 1987)

(untitled) - Hilt, G.; Danz, M.; Treutwein, J. (Org. Lett., 2009)